(untitled) (Quinto Sol, 2019)
This article presents a historiographic summary of the evolution of inequality and the standard of living during the nineteenth century in the future Argentina. Four aspects, closely related, are developed, such as a reflection about the role of the historian in the field, a state of the art and a brief summary of the different methodologies used, a presentation of the main results achieved in Buenos Aires and a description of the historiographical inequality on the subject in the country.